Dysregulation of Immune Regulatory Mediators and Reduced Antitetanus Toxoid Antibodies Are Associated with Submicroscopic Plasmodium Infection in Pregnancy in Colombia - Catalina Álvarez‐Larrotta; Olga M. Agudelo; Jaime Carmona‐Fonseca; Stephanie K. Yanow; Eliana M. Arango (The American Journal of Tropical Medicine and Hygiene, 2026)
ABSTRACT. Infection with Plasmodium falciparum or Plasmodium vivax during pregnancy can result in adverse outcomes for both mother and child. Submicroscopic infections are common in malaria-endemic areas but often remain chronic, asymptomatic, and untreated. Chronic infections persistently stimulate the immune system, altering expression of immune mediators and promoting expansion of regulatory T cells. These immune changes could compromise responses to routine vaccinations. This study evaluated the immunomodulatory effects of submicroscopic infection by P. falciparum and P. vivax during pregnancy and their associations with immune responses to the tetanus toxoid (TT) vaccine. A descriptive, prospective, and longitudinal design was applied to three groups: 1) women infected with malaria during pregnancy but negative at delivery ( n = 50), 2) women with submicroscopic infection at delivery ( n = 48), and 3) uninfected women ( n = 75). Samples were collected between 2008 and 2018 in two regions of Colombia. Women with submicroscopic plasmodial infections and a history of pregnancy-associated malaria were diagnosed by quantitative polymerase chain reaction (qPCR) and thick blood smears. Cytokine expression was quantified by real-time qPCR, and anti-TT IgG levels were measured by ELISA in peripheral blood. Pregnant women with submicroscopic Plasmodium infection exhibited higher expression of IL-10, FoxP3, CTLA4, and TNFRII, indicative of immune regulation. Anti-TT IgG levels were significantly reduced in infected women compared with uninfected women. These findings suggest that submicroscopic Plasmodium infection during pregnancy promotes a regulatory immune profile characterized by expression of immune molecules typical of exhausted T cells and alters immune response to the TT vaccine.